DDX58 Is Associated With Susceptibility to Severe Influenza Virus Infection in Children and Adolescents. (20th August 2022) - Lee, Sanghun; Zhang, Yu; Newhams, Margaret; Novak, Tanya; Thomas, Paul G; Mourani, Peter M; Hall, Mark W; Loftis, Laura L; Cvijanovich, Natalie Z; Tarquinio, Keiko M; Schwarz, Adam J; Weiss, Scott L; et al.
Abstract: Background: Seasonal influenza virus infection causes a range of disease severity, including lower respiratory tract infection with respiratory failure. We evaluated the association of common variants in interferon (IFN) regulatory genes with susceptibility to critical influenza infection in children. Methods: We performed targeted sequencing of 69 influenza-associated candidate genes in 348 children from 24 US centers admitted to the intensive care unit with influenza infection and lacking risk factors for severe influenza infection (PICFlu cohort, 59.4% male). As controls, whole genome sequencing from 675 children with asthma (CAMP cohort, 62.5% male) was compared. We assessed functional relevance using PICFlu whole blood gene expression levels for the gene and calculated IFN gene signature score. Results: Common variants in DDX58, encoding the retinoic acid–inducible gene I (RIG-I) receptor, demonstrated association above or around the Bonferroni-corrected threshold (synonymous variant rs3205166; intronic variant rs4487862). The intronic single-nucleotide polymorphism rs4487862 minor allele was associated with decreased DDX58 expression and IFN signature ( P < .05 and P = .0009, respectively) which provided evidence supporting the genetic variants' impact on RIG-I and IFN immunity. Conclusions: We provide evidence associating common gene variants in DDX58 with susceptibility to severe influenza infection in children. RIG-I may be essential for preventing life-threatening influenza-associated disease. Abstract : Retinoic acid–inducible gene I (RIG-I) is important for type I interferon antiviral host immunity against influenza virus infection. Genetic variants in DDX58 encoding RIG-I may influence this response and susceptibility to severe disease in children.